Concomitant BCORL1 and BRAF Mutations in Vemurafenib-Resistant Melanoma Cells() - Mologni, Luca (Neoplasia, 2018)
BRAF is the most frequently mutated gene in melanoma. Constitutive activation of mutant BRAF(V600E) leads to aberrant Ras-independent MAPK signaling and cell transformation. Inhibition of mutant BRAF is a current frontline therapy for such cases, with improved survival compared with chemotherapy. Unfortunately, reactivation of MAPK signaling by several mechanisms has been shown to cause drug resistance and disease recurrence. In this work, we describe the co-occurrence of an in-frame deletion within an amplified BRAF(V600E) locus and a missense point mutation of the transcriptional repressor BCORL1 in vemurafenib-resistant A375 melanoma cells. Functional data confirmed that truncated p47BRAF(V600E) and mutant BCORL1(Q1076H) both contribute to resistance. Interestingly, either endogenous BCORL1 silencing or ectopic BCORL1(Q1076H) expression mimicked the effects of a CRISPR/Cas9-edited BCORL1(Q1076H) locus, suggesting a complex mixture of loss- and gain-of-function effects caused by the mutation. Transcriptomic data confirmed this hypothesis. Finally, we show that the pan-RAF inhibitor sorafenib is not affected by expression of BRAF deletion variant and effectively synergizes with vemurafenib to block resistant cells, suggesting a possible intervention for this class of mutants.